Polystyrene-b-poly (acrylic acid) nanovesicles coated by modified chitosans for encapsulation of minoxidil - Gilmar Hanck-Silva; Edson Minatti (Universidade de São Paulo, 2022)
Abstract In this work, polystyrene-b-poly (acrylic acid) (PS-b-PAA) nanovesicles were coated by modified chitosans aiming at studying its physicochemical parameters. The chitosan (CS) was chemically modified to add hydrophilic and/or hydrophobic groups, obtaining three modified chitosans. The PS-b-PAA nanovesicles were obtained by organic (1,4-dioxane) cosolvent method in water, resulting in nanovesicles with less than 150 nm of diameter (polydispersibility index - PDI at 90° = 0.106), measured by dynamic light scattering (DLS) and transmission electron microscopy (TEM), and negative zeta potential (-37.5 ± 3.2 mV), allowing the coating of its surface with oppositely charged polysaccharides, such as the CS and the modified chitosans. The coating process was made by mixing the colloidal suspensions with the CS and the modified chitosans at specific ENT#091;CS-xENT#093;/ENT#091;PS-b-PAAENT#093; ratios (0.001 to 1.0 wt %) and measuring the change in size and surface charge by DLS and zeta potential. Upon reaching maximum adsorption, the zeta potential parameter was positively stabilized (+26.7 ± 4.1 mV) with a hydrodynamic diameter slightly longer (< 200 nm of diameter). The encapsulation efficiency (EE) of minoxidil, quantified by capillary electrophoresis, was 50.7%, confirming their potential as drug delivery carriers and the coating process showed the possibility of controlling the surface charge nature of these nanovesicles.